Response of wood decomposition to different forms of N deposition in subtropical forests - Wu, Chunsheng; Shu, Chunjie; Yuan, Xi; Deng, Bangliang; Shen, Fangfang; Zhang, Yi; Liu, Yuanqiu (Frontiers in Forests and Global Change, 2023)
Wood decomposition plays an important role in ecosystem soil fertility and nutrient cycling, but how different forms of nitrogen (N) affect these biogeochemical processes is still unclear. The effects of N deposition on wood decomposition have been widely studied, but the decomposition process and biotic driver response to different forms of N have rarely been studied. In this study, we conducted a two-year field factorial fertilization experiment with different N forms in a subtropical Chinese forest. Glycine and urea were selected as organic N (ON), and ammonium nitrate was selected as inorganic N (IN). Six different ratios (control, 0:10, 3:7, 5:5, 7:3, 10:0) of IN:ON with equal N amounts were uniformly added to the studied wood. We found that both forms of N deposition, i.e., ON and IN, accelerated the wood decomposition rates across the four studied species, and the magnitude of the increase was species specific. Mixed fertilizer with ON and IN resulted in the highest responses in the wood decomposition rate, which was 1.73- and 1.48-fold higher than that in the control and in response to IN addition alone across species. The ON + IN treatment resulted in the highest faunal and microbial community abundance of the decomposing wood. In summary, our results indicate that different forms of anthropogenic N enrichment can promote wood decomposition through the modification of microbial and faunal communities in the wood decomposition process. Our results show that future studies need to consider N forms and components when estimating exogenous N deposition effects on the woody material nutrient cycle and terrestrial ecosystem carbon cycles.